A new species of Mountain Viscacha (Chinchillidae: Lagidium Meyen) from the Ecuadorean Andes - Ledesma, Karim J.; Werner, Florian A.; Spotorno, Angel E.; Albuja, Luis H. (Zootaxa, 2009)
A new species of mountain viscacha, Lagidium ahuacaense, is described based on a specimen and a mitochondrial cytochrome b (cyt b) sequence obtained from a second individual from Cerro El Ahuaca, Loja Province, Ecuador. In several external and craniodental measurements, the new species differed significantly from the three congeneric species (greatest length of skull, basilar, nasal length, palatilar length, length of diastema, least interorbital breadth, breadth of rostrum and skull height). The cyt b sequence of the Ecuadorean viscacha differed by 14 exclusive nucleotide substitutions from all other sequences of Lagidium examined. Kimura 2-parameter (K2P) genetic distances of the Ecuadorean sequence were 8.1–11.0% to L. peruanum, 7.9–9.9% to L. viscacia and 9.7% to L. wolffsohni. The single known population of the newly described species may not comprise more than a few dozen individuals and warrants urgent conservation actions.